UPAYA MENINGKATAKAN HASIL BELAJAR MATEMATIKA MATERI PENJUMLAHAN BILANGAN BULAT DENGAN MENGGUNAKAN METODE PERMAINAN CONGKLAK - SYAHRINA ANISA PULUNGAN (LP2MTBM MAKARIOZ, 2020)
The research aims to find out efforts to improve the results of learning Mathematics integer summing materials using gamemethods. This research was conducted on grade V elementary school students who were 25 students. This type of researchis class action research through four stages: planning, implementation, observation, and reflection. Data collectiontechniques use observations, interviews, field notes, tests and documentation. Data analysis is done descriptively with themean (average) and percentage of overall completion of students. The results of the study can be concluded that there is animprovement in students' learning outcomes. This increase can be seen from the average grade value increased from precycleresults of 66.72 in cycle I the average grade rose to 69.54 and in cycle II rose to 77.72. In pre-cycle the overallcompletion percentage of students was 18% or 4 out of 22 students. In cycle I the percentage of overall completion ofstudents increased to 50% or 11 out of 22 students, then in cycle II increased back to 86% or 19 out of 22 students. Basedon the data, it can be concluded that there is an improvement in the learning achievement of Mathematics starting from thepre-cycle stage, Cycle I and Cycle II. Thus the use of game methods is able to improve the learning results of Mathematics inthe integer summation material of grade V elementary school students.